2018
DOI: 10.14715/cmb/2018.64.10.21
|View full text |Cite
|
Sign up to set email alerts
|

Nesfatin-1 and irisin levels in response to the soccer matches performed in morning, afternoon and at night in young trained male subjects

Abstract: This study aimed to investigate the potential effects of acute soccer matches performed in morning, afternoon and at night on both nesfatin-1 and irisin levels in trained subjects. Total of 20 male subjects performed in soccer matches at three different times of day: morning, afternoon, and night. Pre-and post-match venous blood samples were taken, and levels of both nesfatin-1 and irisin were analysed using the enzyme-linked immunosorbent assay (ELISA). Following all matches, the subjects' irisin levels incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 29 publications
2
8
0
Order By: Relevance
“…A previous study demonstrated that serum nesfatin-1 and insulin sensitivity in obese men were increased after upper-body resistance exercise was conducted (Mogharnasi et al, 2019b ). Altogether, our results are consistent with the previous studies that showed an upsurge in nesfatin-1 and insulin sensitivity following high-intensity training (Ahmadizad et al, 2015 ; Ozcelik et al, 2018 ; Mogharnasi et al, 2019b ). Moreover, another study reported that the reduction in nesfatin-1 induced by a high-fat diet is suppressed by the running wheel in mice (Chaolu et al, 2011 ).…”
Section: Discussionsupporting
confidence: 93%
“…A previous study demonstrated that serum nesfatin-1 and insulin sensitivity in obese men were increased after upper-body resistance exercise was conducted (Mogharnasi et al, 2019b ). Altogether, our results are consistent with the previous studies that showed an upsurge in nesfatin-1 and insulin sensitivity following high-intensity training (Ahmadizad et al, 2015 ; Ozcelik et al, 2018 ; Mogharnasi et al, 2019b ). Moreover, another study reported that the reduction in nesfatin-1 induced by a high-fat diet is suppressed by the running wheel in mice (Chaolu et al, 2011 ).…”
Section: Discussionsupporting
confidence: 93%
“…In the present study we have found systematically increase in irisin levels in all female subjects. In concordance with the results of many previous studies performed in male and female, it is logical to emphasise that irisin is undeniably exercise hormone (8,(13)(14)(15)27,28).…”
Section: Discussionsupporting
confidence: 83%
“…There is an increasing interest among the investigators concerning with exercise induced increase in energy regulatory hormones of nesfatin-1 and irisin (13)(14)(15). It is also known that exercise induced increased metabolic and muscle activity enhance oxidative stress levels (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of conducting this review is to assess the existing research evidence regarding the impact of exercise on Nucleobindin-2 (NUCB2) gene expression and Nesfatin-From the 36 included studies, 23 examined humans with 13 examining animal models. [64][65][66][67][68][69][70][71][72][73][74][75][76] Studies investigated the effects of chronic exercise training [41][42][43][44][45][46][47][48][49][50][51]63 and acute exercise 48,[52][53][54][55][56][57][58][59][60][61][62] in humans.…”
Section: Significance Statementmentioning
confidence: 99%